Warehouse market in Poland in the years 2013-2015 - Piszcz, Anna (Management and Administration Journal, 2019)
The aim of this paper is to present the structure of the warehouse market in Poland in recent years. Explained the essence and concept of the magazine, its functions and types of storage buildings. The article also posted statistics on demand and supply of warehouse space and rents in the major regions of logistics in Poland.